Effect of Coccinia indica leaf extract on angiotensin converting enzyme (ACE) inhibitor induced hepatotoxicity in wistar albino rats. (April 2019) - Vinothkumar, G.; Venkataraman, P.; Vinodhini, V.M.; Lavanya, R.; Sathishkumar, D.
Summary: Enalapril is angiotensin converting enzyme (ACE) inhibitor have been extensively used to treat cardiovascular disorders, including hypertension. Coccinia indica is indigenous plant wildly used in traditional medicinal system including Ayurvedic, Siddha and Unani. The aim of this study was to find out the hepatoprotective activity of C. indica leaf extract against enalapril induced toxic effects. The 24 experimental rats were divided into 4 groups. Group 1 was maintained as control. Group 2 and 3 were treated with single dose of enalapril (1.5g/kg of bwt/orally). After treatment, group 2 maintained as enalapril control. The group 3 was treated with leaf extract of C. indica (400 mg/kg bwt/orally/day) for 7 days. Separate C. indica alone supplementation for 7 days were also maintained. After end of the treatment, animals were sacrificed simultaneously. To determine the serum liver function parameters were estimated. The histophological study of liver tissue was also determined. The changes liver function parameters were observed in enalapril control rats along with histological changes. The C. indica leaf extract supplementation restored all the parameters significantly. In this study, the protective effect of C. indica leaf extract against enalapril induced hepatotoxicity proves, the plant has many medicinal properties. Highlights: Enalapril is angiotensin-converting enzyme (ACE) inhibitor have been extensively used to treat cardiovascular disorders, including hypertension. Indigenous people used various parts of the plant to vegetable. Coccinia indica is indigenous plant wildly used in traditional medicinal system including Ayurvedic, Siddha and Unani. C. indica leaf extract against enalapril induced hepatotoxicity proves, the plant has many medicinal properties.